Determination of the light yield of organic scintillators - Galunov, N.Z.; Tarasenko, O.A.; Tarasov, V.A. (Functional Materials, 2013)
The paper analyzes the reasons of a distinction in the values of the light output and the light yield obtained by different authors for organic scintillators. The comparison method was used to determinate update values of the light output and the light yield for organic single crystals of anthracene, stilbene, p-terphenyl and plastic scimtillator on the base on polystyrene. These data correspond to characteristics of similar objects created in the Institute for Scintillation Materials, National Academy of Sciences of Ukraine, that are cited in the works of our foreign colleagues. By an example of stilbene crystals obtained by the same technology, it was shown that the spread in the light output values did not exceed 10 %.